FRAMING PEMBERITAAN JATUHNYA PESAWAT HERCULES TNI AU A1310 PADA MEDIA ONLINE THE JAKARTA POST EDISI JUNI - JULI 2015 - Nugroho, Ari Cahyo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
The crash of Hercules plane with flight number A1310, has preached various media. The Jakarta Post online, is Indonesia?s largest english version online media, accessible by 4.7 million users. This framinganalysis the crash of Hercules plane with flight number A1310 on Online Media The June edition of The Jakarta Post-July 2015 with Framing model Robert N Etmant. The results showed that Jakarta Post news framing refers to selection issues, aspects of issues, defining problem, estimate problem or source of problem, and moral decision making.In selection of issues, Jakarta Post concerning humane aspects, the feelings of events. Jakarta Post didn?t browse further ?conspiracy? in Hercules seat sale, it seem TNI AU is the symbol of a government that does not seek profit. In a particular aspect of Jakarta Postissue, it appears the majority of interviewees obtain TNI (AU). The problem show in the existence of technical problems of the plane (its old fleet of aircraft used). In terms of estimating problem or the source of problem, Jakarta Post seem not to write in depth. Jakarta Post just wrote from the surface. The final decision about making a moral, Jakarta Post writings no moral decision making in news.